A Garment Suggestion Engine Based on Visual Similarity - Göktürk, Mehmet; Kabakli, Bilal; Yogurtcuglu, Hamza (IEEE, 2020)
In this study, a product suggestion engine has been developed for an e-commerce site portfolio focusing on garment items. Traditional collaborative filtering methods usually lack applicability due to high turnover rates in product lists. Thus, by focusing on visual similarity using deep leraning technique successful results were obtained and it has been concluded that application of this technique to real live e-commerce garment site will be suitable.
28th Signal Processing and Communications Applications Conference (SIU) -- OCT 05-07, 2020 -- ELECTR NETWORK
Keywords: deep learning; e-commerce; image processing